EAACI position paper on diet diversity in pregnancy, infancy and childhood: Novel concepts and implications for studies in allergy and asthma. Issue 3 (10th March 2020) - Venter, Carina; Greenhawt, Matthew; Meyer, Rosan W.; Agostoni, Carlo; Reese, Imke; du Toit, George; Feeney, Mary; Maslin, Kate; Nwaru, Bright I.; Roduit, Caroline; Untersmayr, Eva; Vlieg‐Boerstra, Berber; et al.
Abstract: To fully understand the role of diet diversity on allergy outcomes and to set standards for conducting research in this field, the European Academy of Allergy and Clinical Immunology Task Force on Diet and Immunomodulation has systematically explored the association between diet diversity and allergy outcomes. In addition, a detailed narrative review of information on diet quality and diet patterns as they pertain to allergic outcomes is presented. Overall, we recommend that infants of any risk category for allergic disease should have a diverse diet, given no evidence of harm and some potential association of benefit in the prevention of particular allergic outcomes. In order to harmonize methods for future data collection and reporting, the task force members propose relevant definitions and important factors for consideration, when measuring diet diversity in the context of allergy. Consensus was achieved on practice points through the Delphi method. It is hoped that the definitions and considerations described herein will also enable better comparison of future studies and improve mechanistic studies and pathway analysis to understand how diet diversity modulates allergic outcomes.